Bio-Economic Perspective to Fuelwood Policy Options in Uganda: A Demand–Supply Nexus - Buyinza Mukadasi; Masaba Sowedi (Fakultas Kehutanan Universitas Gadjah Mada, 2008)
This study examines the benefits and costs of selected policy options for increasing fuelwood supplies or decreasing fuelwood demand in Hoima district, Uganda. On the supply side, a benefit-cost analysis is done on a government sponsored tree farming project. In order to reduce the demand for fuelwood, two demand-side options are considered, namely, introduction of an improved energy-efficient woodstove, and the substitution of a kerosene stove for a traditional woodstove. Greater understanding of the linkages among these factors requires a systems approach. We have proposed such an approach using a non-linear dynamic programming model to explore the system behaviour of forest degradation. Our results show that tree-farming is one of the possible approaches to increase the supply of fuelwood (energy), while the woodstoves and kerosene substitution are policies that reduce the demand for fuelwood. This helps to alleviate the rural energy shortage and take some pressure off existing protected forest areas. The tree cover in the forest areas declined by 6% in the BASE scenario, 4.8 % in POPG scenario and 4.7% in TECH scenario, indicating an overall trend of forest degradation in the Hoima district under each of these scenarios. Reductions in the population growth rate, introduction of improved agricultural technology and increase in the prices of major agricultural crops can help slow down the rates of forest decline. This study does not attempt to analyse the wider energy planning program that would be needed to understand accurately the various alternatives available in Uganda.